Activation of nano-photosensitizers by Y-90 microspheres to enhance oxidative stress and cell death in hepatocellular carcinoma - Christopher D. Malone; Christopher Egbulefu; Alexander Zheleznyak; Jahnavi Polina; Partha Karmakar; Kvar Black; Monica Shokeen; Samuel Achilefu (Scientific Reports, 2022)
Abstract While radioembolization with yttrium-90 (Y-90) microspheres is a promising treatment for hepatocellular carcinoma (HCC), lower responses in advanced and high-grade tumors present an urgent need to augment its tumoricidal efficacy. The purpose of this study was to determine whether clinically used Y-90 microspheres activate light-responsive nano-photosensitizers to enhance hepatocellular carcinoma (HCC) cell oxidative stress and cytotoxicity over Y-90 alone in vitro. Singlet oxygen and hydroxyl radical production was enhanced when Y-90 microspheres were in the presence of several nano-photosensitizers compared to either alone in cell-free conditions. Both the SNU-387 and HepG2 human HCC cells demonstrated significantly lower viability when treated with low activity Y-90 microspheres (0.1–0.2 MBq/0.2 mL) and a nano-photosensitizer consisting of both titanium dioxide (TiO2) and titanocene (TC) labelled with transferrin (TiO2-Tf-TC) compared to Y-90 microspheres alone or untreated cells. Cellular oxidative stress and cell death demonstrated a linear dependence on Y-90 at higher activities (up to 0.75 MBq/0.2 mL), but was significantly more accentuated in the presence of increasing TiO2-Tf-TC concentrations in the poorly differentiated SNU-387 HCC cell line (p < 0.0001 and p = 0.0002 respectively) but not the well-differentiated HepG2 cell line. Addition of TiO2-Tf-TC to normal human hepatocyte THLE-2 cells did not increase cellular oxidative stress or cell death in the presence of Y-90. The enhanced tumoricidal activity of nano-photosensitizers with Y-90 microspheres is a potentially promising adjunctive treatment strategy for certain patient subsets. Applications in clinically relevant in vivo HCC models are underway.